The Impact of Social Media on Mental Health Among Adolescents (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research investigates the correlation between excessive social media use and mental health issues among adolescents. By examining existing literature and conducting surveys and interviews, the study aims to identify specific social media platforms and features that contribute to mental health problems. Furthermore, it will explore potential coping mechanisms and interventions to mitigate negative impacts